Choosing the optimal method in programmatic colorectal cancer screening: current evidence and controversies. (July 2015) - Castells, Antoni
Colorectal cancer (CRC) is an important health problem all over the world, being the third most common cancer and the second leading cause of cancer-related death in Western countries. The most important strategy for CRC prevention is screening (i.e. secondary prevention). Since it is widely accepted that adenomas and serrated polyps are the precursors of the vast majority of CRC, early detection and removal of these lesions is associated with a reduction of CRC incidence and, consequently, mortality. Moreover, cancers detected by screening are usually diagnosed at early stages and, therefore, curable by endoscopic or surgical procedures. This review will be address CRC screening strategies in average-risk population, which is defined by those individuals, men and women, 50 years of age or older, without any additional personal or familial predisposing risk factor. In order to maximize the impact of screening and ensure high coverage and equity of access, only organized screening programs (i.e. programmatic screening) should be implemented, as opposed to case-finding or opportunistic screening. For that reason and considering that the optimal approach for colorectal screening may differ depending on the scenario, this review will be focused on the advantages and limitations of each screening strategy in an organized setting.